Bioinspired Electrolyte-Gated Organic Synaptic Transistors: From Fundamental Requirements to Applications - Liang, Yuanying; Li, Hangyu; Tang, Hu; Zhang, Chunyang; Men, Dong; Mayer, Dirk (Nano-Micro Letters, 2025)
Rapid development of artificial intelligence requires the implementation of hardware systems with bioinspired parallel information processing and presentation and energy efficiency. Electrolyte-gated organic transistors (EGOTs) offer significant advantages as neuromorphic devices due to their ultra-low operation voltages, minimal hardwired connectivity, and similar operation environment as electrophysiology. Meanwhile, ionic–electronic coupling and the relatively low elastic moduli of organic channel materials make EGOTs suitable for interfacing with biology. This review presents an overview of the device architectures based on organic electrochemical transistors and organic field-effect transistors. Furthermore, we review the requirements of low energy consumption and tunable synaptic plasticity of EGOTs in emulating biological synapses and how they are affected by the organic materials, electrolyte, architecture, and operation mechanism. In addition, we summarize the basic operation principle of biological sensory systems and the recent progress of EGOTs as a building block in artificial systems. Finally, the current challenges and future development of the organic neuromorphic devices are discussed. Highlights: 1 Neuromorphic device with bioinspired parallel information processing and presentation and energy efficiency is desired for the rapid development of artificial intelligence. 2 Electrolyte-gated organic transistors can be leveraged to emulate versatile synaptic functions with tunable properties and excellent biocompatibility. 3 Recent development regarding the organic channel materials, neuromorphic device handling neurochemical signals, the basic requirements to achieve artificial synapse, and the applications on mimicking perception functions are reviewed.